Reproductive timing as a constraint on invasion success in the ring-necked parakeet (Psittacula krameri) - Luna, Alvaro; Braun, Michael P. (Biological invasions, 2017)
Climate similarity favors biological invasion, but a match between seasonality in the novel range and the timing of life cycle events of the invader also influences the outcome of species introduction. Yet, phenology effects on invasion success have generally been neglected. Here we study whether a phenological mismatch limits the non-native range of a globally successful invader, the Ring-necked parakeet, in Europe. Given the latitudes at which parakeets have established across Europe, they breed earlier than expected based on breeding dates from the native Asian range. Moreover, comparing the breeding dates of European populations to those of parakeets in the native Asian range, to five native breeding bird species in Europe and to the start of the growing season of four native European trees shows that the discrepancy between expected and actual breeding phenology is greater in northern Europe. In northern European populations, this temporal mismatch appears to have negative effects on hatching success, and on population growth rates in years that are colder than average in the first six months. Phenological mismatch also can explain why parakeets from African populations (that are more likely to breed in autumn) have been poor invaders compared to parakeets from Asia. These lines of evidence support the hypothesis that the reproductive phenology of the Ring-necked parakeet can be a limiting factor for establishment and range expansion in colder climates. Our results provide growing support for the hypothesis that the match between climate seasonality and timing of reproduction (or other important life cycle events) can affect the establishment success, invasive potential and distribution range of introduced non-native species, beyond the mere effect of climate similarity.